Weissella confusa alleviates experimental colitis in mice by regulating inflammatory pathways and gut microbiota - Tang, Huijing; Fan, Qianhua; Lu, Yao; Lin, Xiaoying; Lan, Ruiting; Hu, Dalong; Zhang, Shuwei; Wang, Ruoshi; Zhao, Ruiqing; Liu, Liyun; Xu, Jianguo (Frontiers in Microbiology, 2025)
BackgroundInflammatory bowel disease (IBD) is a chronic condition with no cure. Probiotics may offer a new strategy for the treatment of IBD. Weissella confusa has been shown to have antibacterial, anti-inflammatory, and antioxidant beneficial effects in animal models. However, the anti-inflammatory effect of W. confusa at host cellular level and their effect on the gut microbiota are unclear. This study aimed to investigate the effects of W. confusa Wc1982 on inflammation and gut microbiota alterations in a dextran sulfate sodium (DSS) induced colitis mouse model.MethodFemale C57BL/6J mice were randomly divided into control, DSS, and Wc1982 groups (n = 6/group). The Wc1982 group was given continuous gavage of W. confusa Wc1982 for 14 days with the last 7 days also treated with 3% DSS. Disease phenotypes including daily body weight, disease activity index (DAI), colon length and histological changes were evaluated. The composition of colon flora, α-diversity and β-diversity were analyzed by 16S rRNA sequencing. The colonic gene expression profile was analyzed by RNA-seq, and serum and colonic proinflammatory cytokines were assessed by enzyme-linked immunosorbent assay. Analysis of variance (ANOVA) was used to analyze the differences among groups, and Spearman rank test was used to calculate the correlation between species relative abundance and pro-inflammatory markers.ResultsCompared with DSS group, W. confusa Wc1982 significantly improved the disease phenotypes of colitis mice including decreased DAI and pathological score and reduced colon shortening, decreased colonic IL-17, IL-6, and TNF-α levels and serum lipopolysaccharide (p < 0.05), and downregulated the expression of key genes of IL-17 pathway (Lcn2, Mmp3, Mmp13, Ptgs2; p < 0.05). W. confusa Wc1982 modified the gut microbiota community of colitis mice, with increased α-diversity, increased abundance of W. confusa and Akkermansia muciniphila, and decreased abundance of Enterococcus faecalis and Escherichia coli (all p < 0.05).ConclusionSupplementation with W. confusa Wc1982 offers a promising strategy for alleviating colitis.